2016
DOI: 10.1007/s00737-016-0706-5
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal suicidal ideation and behaviour: psychiatry and adversity

Abstract: Pregnant women are at increased risk for suicidal ideation and behaviours (SIB) compared to the general population. To date, studies have focused on the psychiatric correlates of SIB with lesser attention given to the associated contextual risk factors, particularly in low- and middle-income countries. We investigated the prevalence and associated psychiatric and socio-economic contextual factors for SIB among pregnant women living in low resource communities in South Africa. Three hundred seventy-six pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
83
2
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 86 publications
16
83
2
6
Order By: Relevance
“…These associations have been described and discussed in detail elsewhere (Onah et al . 2016 a , b; van Heyningen et al . 2016, 2017; Field et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These associations have been described and discussed in detail elsewhere (Onah et al . 2016 a , b; van Heyningen et al . 2016, 2017; Field et al .…”
Section: Resultsmentioning
confidence: 99%
“…Also, analysis of the dataset showed that a large proportion of women with suicidal thoughts and/or behaviour had neither depression nor anxiety diagnoses (Onah et al . 2016 a ). SIB that occurs outside of the context of depression and anxiety diagnosis is an important public health issue, and has been described in greater detail in another paper arising from the same dataset (Onah et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where such ultra short screening instruments are used, it is advised to follow-up with more in-depth screening or clinical assessment. This is especially important considering the high rate of women expressing suicidal ideation and behaviour [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…These critiques have spurned a number of studies which have attempted to examine more broadly the role of contextual factors in the aetiology of suicide. Examples include the systematic review on the relationship between poverty and suicidal behaviour in LMICs ( Iemmi et al, 2016 ) and a study among perinatal women living in a low-resource environment in SA which found that socio-economic adversity was a better predictor of suicidal behaviour than psychiatric conditions ( Onah et al, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%